Locust : the Devastating Rise and Mysterious Disappearance of the Insect that Shaped the American Frontier. - Lockwood, Jeffrey A. (Basic Books, 2009)
In 1876, the U.S. Congress declared the locust "the single greatest impediment to the settlement of the country between Mississippi and the Rocky Mountains." Throughout the nineteenth century, swarms of locusts regularly swept across the American continent, turning noon into dusk, devastating farm communities, and bringing trains to a halt. The outbreaks subsided in the 1890s, and then, suddenly--and mysteriously--the Rocky Mountain locust vanished. A century later, entomologist Jeffrey Lockwood vowed to discover why. Locust is the story of how one insect shaped the history of the wes.